Current Issues and Perspectives in Antimicrobials use in Dental Practice - Santacroce, Luigi; Spirito, Francesca; Bottalico, Lucrezia; Muzio, Eleonora L.; Charitos, Ioannis Alexandros; Potenza, Maria Assunta; Montagnani, Monica; Jirillo, Emilio (Current Pharmaceutical Design, 2022)
The complexity of the use of antimicrobials for dental use (such as antibiotics) is directly related not only to the mode of onset of an oral infection (linked to numerous factors of local causality and comorbidity) but also to the predisposing risk for the general health of the patient with putative serious consequences related to the neck district. The abuse and misuse of antibiotics may lead to resistance to certain bacterial strains. In this regard, the evaluation of the risk/benefit of their use (especially in pregnant women) can be divided into two phases: risk analysis and subsequently risk management for the benefit of the patient for the oral pathology to be prevented or treated, respectively. This study seeks to focus on the issues and management of patients with certain antimicrobials during dental practice, placing special emphasis on new classes of antibiotics.
Keywords: antibiotics